PENGARUH MANAJEMEN USAHA DAN MUROTAL AL-QUR’AN SERTA FAKTOR EKONOMI TERHADAP PRODUKSI USAHA TERNAK AYAM BROLIER - Suwarta Suwarta; Darmadji Darmadji (University of Jember, 2020)
This study aims to determine: (1) the factors that influence the production of broiler chicken farming, (2) the effect of broiler chicken business management on production, and (3) the effect of murotal Al-Qur'an and other production factors on production. This research was conducted in Malang Regency, with the consideration that Malang Regency is one of the three (3) big broiler-producing districts in East Java. As the unit of analysis is primary data from interviews with broiler breeders who were selected as respondents. The analysis tool uses multiple linear regression models using the natural form (Ln). The results showed that: (1) The production of broiler chicken farming was positively influenced by the number of seeds, the amount of feed, business management, business capacity, murotal Al-Qur'an and the volume of business above the average. Broiler chicken production is negatively affected by the area of ​​the house, the number of dead chickens, and the number of abandoned chickens. Independent variables that do not affect the production of broiler chicken farming are the management of broiler chicken raising and the number of person working days (HKO). To increase production, it is necessary to increase the number of seeds, the amount of feed, optimize the area of ​​the cage, reduce the number of dead chickens, reduce the number of dead chickens, improve business management, increase business capacity, utilize murotal Al-Qur'an and with business volume above average. Keywords: Production, management, livestock business, murotal Al-Qur'an, broiler chickens